Translational pharmacology of an inhaled small molecule αvβ6 integrin inhibitor for idiopathic pulmonary fibrosis - Alison E. John; Rebecca H. Graves; K. Tao Pun; Giovanni Vitulli; Ellen J. Forty; Paul F. Mercer; Josie L. Morrell; John W. Barrett; Rebecca F. Rogers; Maryam Hafeji; Lloyd I. Bibby; Elaine Gower; et al. (Nature Communications, 2020)
The αvβ6 integrin is key in activating the pro-fibrotic cytokine TGFβ in idiopathic pulmonary fibrosis. Here, the authors show an inhaled small molecule αvβ6 inhibitor GSK3008348 induces prolonged inhibition of TGFβ signaling pathways in human and murine models of lung fibrosis via αvβ6 degradation.